Glass House: Bedford, New York (Oz, 2003)
This project began when a young family, residing in New York City, decided to leave the city and raise their family in a more bucolic setting. They purchased several plots of land and pieced them together into a contiguous twenty-six-acre plot of rolling wooded hills that culminates at a rocky ridge with sweeping views of a protected nature preserve.